Investigation of a prolonged APTT. Different approaches taken by laboratories to achieve the same diagnosis. Issue 2 (1st November 2012) - Jennings, I.; Kitchen, D. P.; Kitchen, S.; Woods, T. A. L.; Walker, I. D.
Summary: Introduction: The APTT is widely employed as part of a coagulation screening panel, used as a pre‐operative assessment of bleeding risk, to detect hereditary and acquired haemostatic defects and to monitor anticoagulant therapy. External quality assessment (EQA) exercises assess laboratory performance of individual tests, but rarely assess the approach to investigation of an abnormal result. Methods: A multicentre exercise was carried out to investigate the ability of laboratories to identify the cause of a prolonged APTT. A sample was distributed with a request to carry out whichever tests were considered necessary to achieve a probable diagnosis. Results: One hundred and ten centres in the UK NEQAS programme took part, and all 104 centres providing an interpretation correctly identified deficiency of FVIII in the sample. However, of these, 10 centres reported additional defects, including lupus anticoagulant, FIX deficiency, FXII deficiency and a FVIII inhibitor. Conclusions: A markedly varied approach to investigation of a prolonged APTT was observed, although a lack of clinical information may have contributed to this finding.